A THE ROLE OF PARENTS IN GROWING CHILDREN'S LEARNING INTEREST IN ONLINE IPS LESSONS DURING THE PANDEMI IN DI SMPN 2 PALIYAN: - - Segoro, Adi Ranto Telong; Siswanta (KARMAWIBANGGA Historical Studies Journal, 2023)
ABSTRACT Research objectives: (1) The role of parents to foster children's learning interest in online social studies learning during the covid-19 pandemic, (2) Supporting factors for parents to foster children's interest in learning online during the Covid-19 pandemic, (3 ) Factors inhibiting parents from growing children's learning interest in online learning during the Covid-19 pandemic, (4) Solutions to overcome parental barriers to foster children's interest in learning in online learning during the Covid-19 pandemic. This type of qualitative descriptive research. The research subjects were: parents and students of class VIII SMP N 2 Paliyan. The research was conducted at SMP N 2 Paliyan on May 15 to July 30, 2022. Data collection techniques: observation, interviews, and documentation. Data analysis techniques: data reduction, data exposure, and verification. Test the validity of the data in this study using a credibility test by increasing persistence and triangulation: sources, techniques and time. The results of the study: (1) The role of parents to foster children's interest in learning by providing enthusiasm, motivation, encouragement, supervising, and accompanying children during learning. (2) The factors that support parents in growing children's interest in learning are that children can follow, understand, do not fall behind in lessons, get good grades, and become smart children. (3) The inhibiting factor for parents is that not all parents master cell phones and lack understanding of learning materials. (4) The solution to overcome obstacles is that parents invite their children to read books, search for materials through the internet, ask for help from the community, and ask the teacher.Keywords: Role of Parents, Interest in Social Studies Learning, Online Learning, Covid-